MIXING SPORTS AND POLITICAL JOURNALISM: MODERN COMMUNICATION TECHNOLOGIES - Nikonov, S.B.; Kaverina, E.A.; Puyu, A.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify communication technologies that are used to broadcast political discourses in the sports field and in sports journalism. Methods and structure of the study. During the work on the article, the methods of theoretical and system analysis, participant observation were used. The relevance of the work lies in the fact that in the context of globalization, sports and sports journalism are becoming important political, social and economic factors that require an interdisciplinary and systematic approach when studying. Results and conclusions. A hypothesis has been developed about the changing role of sports journalism due to the fact that sports events and sports content are engaged by geopolitical brands, media business and focused on solving strategic and operational external and internal political tasks. The communication technologies that are used to mix the discourses of sports and political journalism are defined. These communication technologies include: branding technologies, creation of special events, storytelling and infotainment technologies.